THE POTENTIAL OF ROOFTOP SOLAR POWER PLANTS AS AN ENVIRONMENTALLY FRIENDLY ENERGY SOURCE FOR RESIDENTS IN MEDAN CITY - Siti Anisah; Zuraidah Tharo (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This paper aims to analyze the potential and sustainability of solar power plants as an environmentally friendly energy source in residential areas in Medan. Medan, as a major city in North Sumatra, has a tropical climate that tends to be hot throughout the year and is exposed to abundant sunlight. Therefore, the potential for utilizing solar power as an alternative energy source in Medan is very interesting to investigate. The research method used involved a field survey to identify the number and type of residences in Medan City as well as the physical environmental conditions that affect the efficiency and effectiveness of solar power plants utilization. In addition, an analysis of historical data on electricity consumption in residential areas was also conducted to evaluate the potential energy savings that can be achieved through solar power plants implementation. The results of this study are expected to provide a better understanding of the potential use of solar power plants in residential areas in Medan City and its implications for the environment and quality of life. It is also expected to provide recommendations for stakeholders, including the government and the community, to consider the use of solar power plants as an environmentally friendly alternative energy source in an effort to increase energy independence and reduce negative impacts on the environment. By implementing solar power plants as a primary or complementary energy source in residential areas, it is expected to improve energy sustainability, reduce greenhouse gas emissions, and reduce dependence on fossil fuels. In addition, this study can also serve as a basis for further research on solar power plant system optimization, policy implementation, and economic modeling related to solar energy use in Medan City.